Effect of Two Sheet Piles In Double Soil Layers on Seepage Properties Under Hydraulic Structure Using SEEP/W Program - Jamel, Asmaa Abdul Jabbar (Al-Nahrain Journal for Engineering Sciences, 2017)
This paper is intended to study the effect of using upstream and downstream sheet pile in double soil layer on the seepage, uplift pressure exit gradient at toe of hydraulic structure using computer program SEEP/W software._x000D_ Depended on the software program tests were carried out with three different value of each following parameter: upstream sheet pile depth, downstream sheet pile depth, permeability for first and second soil layer, depth of first and second soil layer, with using constant upstream head and distance between the two sheet pile. For each test the quantity of seepage, exit gradient and uplift pressure at toe of hydraulics structure were determined. Based on the results of these runs an empirical equations developed to determine the quantity of seepage, uplift pressure and exit gradient at toe of hydraulic structure by using SPSS software. Also, Verify the SEEP/W results and the suggested equations with artificial neural network (ANN). The verification show difference less than 5% , 2% and 6% for exit gradient, discharge and uplift pressure respectively at toe of hydraulic structure.